Association of overweight, obesity and risk of urinary incontinence in middle-aged and older women: a meta epidemiology study - Shang, Xin; Fu, Yu; Jin, Xiaoqin; Wang, Chenxiao; Wang, Ping; Guo, Panpan; Wang, Ying; Yan, Shuxun (Frontiers in Endocrinology, 2023)
The aim of this meta-analysis is to evaluate the potential correlation between obesity and overweight, and the vulnerability to urinary incontinence (UI) in women aged middle-aged and above.We searched PubMed, Cochrane Library, and Embase for observational studies published between the inception of the databases and April 25, 2023. A fixed-effects model was used when the P＞0.1 and the I 2 ≤ 50%. In cases where I 2 ≥ 50% (indicating significant heterogeneity), a randomeffects model was applied. For the purpose of evaluating publication bias, a funnel plot and Egger's test were used. Stata 14.0 was used for all statistical analyses. Findings： This meta-analysis includes 16 observational studies, covering29,618 individuals. The pooled analysis shows that being overweight(25 kg/m 2 ≤BMI＜30kg/m 2 ) in middle-aged and elderly women is more likely to develop UI (OR=1.27; 95% CI: 1.17-1.37; I 2 =51.8%, P=0.013). Middleaged and elderly women with obesity(30 kg/m 2 ≤BMI＜35 kg/m 2 ) are significantly more likely to develop UI (OR=1.60; 95% CI: 1.42-1.81; I 2 =71.8%, P=0.000). In addition, the results indicated a higher probability of UI in middle-aged and older women with obesity class II (BMI≥35 kg/m 2 ) (OR=1.85; 95% CI: 1.59-2.16; I 2 =48.1%, P=0.103). In subgroup analysis, there is no direct relationship between the obesity in middle-aged and elderly women and an increased risk of stress urinary incontinence (SUI) (OR=1.31; 95% CI: 0.99-1.74; I 2 =63.7%, P=0.011). In middle-aged and This is a provisional file, not the final typeset article elderly women with obesity are more likely to develop urgent urinary incontinence (UUI) (OR=2.11; 95% CI: 1.54-2.89; I 2 =80.2%, P=0.000).In this meta-analysis, overweight and obesity are associated with an increased risk of UI in middle-aged and elderly women. Obesity and overweight are independent risk factors for UI, as demonstrated by this study.